Power system design for solar car - Sunil Shanaz, Redzuan Perpinder (2010)
The solar car power system consists of three main subsystems which are the solar array, battery management and lastly, battery pack. It is arguably the most essential system of a solar car since it generates power for the car thus vastly influences the functionality of the car itself. This project was carried out to design a solar car power system that is feasible, cost effective and in compliance with the rules and regulations of the 2011 World Solar Challenge (WSC). The main objective of this project was to design an electrical layout of a solar car power system with components that are properly selected as well as carrying out analysis to determine the practicality and compatibilty of the design. The design of the power system was divided into four levels which were the selection of subsystems’ mian components, design of the subsystems, the conditioning of the power system and finally, the design of the overall power system itself. These steps involved drawing of design, design calculations and analysis of compatibilty within the power system. The drawings involved in the design of the system were done via Solidworks 2010 and SmartDraw 2010 softwares. The finalized design delivered a power system that could generate a maximum power of 837.6W through its solar array designed by tabbed monocrystalline solar cells. The power generated would be stored in a battery pack which consists of five VRLA batteries with a combined power capacity of 6.4kWh. A buck type maximum power point tracker configures the input from the solar array to the battery pack. Motor controller of the actuation system would configure the power system to continuously supply 1kW to the motor. It is calculated that in ideal conditions, the power system can continously power the motor for at least 11.99 hours which is already sufficient for a day of solar racing. The results and discussion concluded that the design of the solar car power system is feasible to be implemented and is considerably cost effective, within the financial prowess of the university. Through proper justifications, the design is also proven to be compatible within the system itself. For further improvements in the future, this project should be conducted with a greater budget so that rather than coming up with a conceptual design, a fabrication or at least a better form of design simulation can be done. Besides that, with greater budget, better components that are more costly are then affordable.